データベース付きオープンアクセスジャーナル「Human Genome Variation」の出版：日本人類遺伝学会の取り組み - 徳永, 勝士 (Journal of information processing and management, 2018)
In the fields of human genetics or medical genomics, the need of "data sharing" is increased not only for facilitating research activities but also for realizing clinical genomic medicine. Since 2014, the Japan Society of Human Genetics has been publishing an open access journal "Human Genome Variation" accompanying the journal's own database. The concept of the journal as well as its present and future prospects are described.